The aryl hydrocarbon receptor-mediated and genotoxic effects of fractionated extract of standard reference diesel exhaust particle material in pulmonary, liver and prostate cells - Pálková, Lenka; Vondráček, Jan; Trilecová, Lenka; Ciganek, Miroslav; Pěnčíková, Kateřina; Neča, Jiří; Milcová, Alena; Topinka, Jan; Machala, Miroslav (Toxicology in vitro, 2015)
Diesel exhaust particles (DEP) and the associated complex mixtures of organic pollutants, such as polycyclic aromatic hydrocarbons (PAHs), or their derivatives, have been suggested to exert deleterious effects on human health. We used a set of defined cellular models representing liver, lung and prostate tissues, in order to compare non-genotoxic and genotoxic effects of crude and fractionated extract of a standard reference DEP material - SRM 1650b. We focused on the aryl hydrocarbon receptor (AhR)-mediated activity, modulation of cell proliferation, formation of DNA adducts, oxidative DNA damage, and induction of DNA damage responses, including evaluation of apoptosis, and phosphorylation of p53 tumor suppressor and checkpoint kinases (Chk). Both PAHs and the polar aromatic compounds contributed to the AhR-mediated activity of DEP-associated organic pollutants. The principal identified AhR agonists included benzo[k]fluoranthene, indeno[1,2,3-c,d]pyrene, chrysene and several non-priority PAHs, including benzochrysenes and methylated PAHs. In contrast to PAHs, polar compounds contributed more significantly to overall formation of DNA adducts associated with phosphorylation of p53, Chk1 or Chk2, and partly with apoptosis. Therefore, more attention should be paid to identification of DEP-associated polar organic compounds, contributing to the AhR activation and cytotoxic/genotoxic effects of complex airborne mixtures of organic contaminants produced by diesel engines.
Keywords: Liver; Animals; DNA Damage; apoptóza; prostata; Lung; výfukové emise vozidel; játra; Prostate; Apoptosis; Cell Cycle; receptory aromatických uhlovodíků; adukty DNA; Vehicle Emissions; mutageny; Particulate Matter; buněčná smrt; buněčný cyklus; Receptors, Aryl Hydrocarbon; poškození DNA; Male; Air Pollutants; DNA Adducts; Cell Death; krysa rodu Rattus; plíce; Mutagens; zvířata; mužské pohlaví; látky znečišťující vzduch; Rats; pevné částice